2017
DOI: 10.1002/mma.4654
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a one‐dimensional wave equation with variable coefficient under non‐collocated control and delayed observation

Abstract: In this paper, we consider stabilization of a 1-dimensional wave equation with variable coefficient where non-collocated boundary observation suffers from an arbitrary time delay. Since input and output are non-collocated with each other, it is more complex to design the observer system. After showing well-posedness of the open-loop system, the observer and predictor systems are constructed to give the estimated state feedback controller. Different from the partial differential equation with constant coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Later, this method had been the main tool to deal with variable coefficient problems . Yang considered stabilization of a 1‐dimensional wave equation with variable coefficient where noncollocated boundary observation suffers from an arbitrary time delay. By the approach of Riesz basis property, it is shown that the closed‐loop system is stable exponentially.…”
Section: Introductionmentioning
confidence: 99%
“…Later, this method had been the main tool to deal with variable coefficient problems . Yang considered stabilization of a 1‐dimensional wave equation with variable coefficient where noncollocated boundary observation suffers from an arbitrary time delay. By the approach of Riesz basis property, it is shown that the closed‐loop system is stable exponentially.…”
Section: Introductionmentioning
confidence: 99%